MACHINE LEARNING METHODS FOR IMPROVING THE QUALITY OF IMAGES FROM RAILWAY SURVEILLANCE CAMERAS - Akhmetov Б.С.; Isaykin Д.В; Bereke М.Б (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article shows the development of the methodology for changing the resolution (RD) of images received from cameras video surveillance on railway transport. Studies were conducted based on the application of machine learning (MLM) and genetic algorithm (GA) in image processing. Through to the implementation of this approach it was able to expand the functionality of the MLM. In particular, it is proposed to implement the process of oversampling with the target coefficient of information content of image frames using GA. The article describes the implementation of the hardware and software part of the developed video surveillance system based on the Raspberry Pi. Also article shows the implemented software module GUI PP ImageScaling.exe in algorithmic languages Python and C #.